Analysis of the sedimentation of the cretaceous system of the Andes of Central Peru - Jacay Huarache, Javier Pablo (2012)
The system Cretaceous in the Andes of the central Peru lies unconformity on lands of different ages, from the Precambrian until the upper Jurassic on which is presented in three big sequences: an lower sequence (Valanginian- Aptian) that belongs to the siliciclastics platform of the Goyllarisquizga Group and its equivalent ones lateral according to the places, in which a clear eastern provenience is denoted, likewise for the units stratigrphics that conform this great delta a deposit it is noticed in lateral onlap on the borders of the basin; a second sequence of the Albian-Turonian to the Campanian that belongs to a great platform carbonated (Jumasha; Chonta formations and equivalents) and the third sequence to the end of the upper Cretaceous (Campanian-Maestrichtian) composed by the continental red beds that belong to processes of tectonic inversion and transition to foreland basins. During the development of this system you can appreciate a high subsidence on the western edge that comes to be the bank area and the border of the platform, while toward the high of the Marañon one has a reduced thickness denoting to be an area with smaller subsidence (Outer Shelf High), and on the current oriental basin and area subandean, it corresponded to an area of moderate subsidence; the arrival of clastics sediments to the Valanginian of clear eastern coming (Brazilian and Guyanense shield) it would be bound to the opening of the rift of the middle Atlantic.These sedimentary sequences that were developed on the platform, limited to the west with a bound arch magmatic to an oblique subduction that is developed in a extensional regime, in which can differ to the Casma Group and basins type pull apart, especially on the edge northwestern.